0002 Decreased Concentration of Klotho and Increased Concentration of FGF-23 in the Cerebrospinal Fluid of Patients with Narcolepsy. (27th May 2020) - Oliveira, G P; Elias, R M; Fernandes, G B; Moyses, R; Tufik, S; Bichuetti, D B; Coelho, F M
Abstract: Introduction: Narcolepsy is a disorder characterized by hypersomnolence, cataplexy, sleep paralysis, hallucinations and sleep fragmentation. Patients with type 1 narcolepsy have cataplexy and/or hypocretin-1 deficiency. Klotho is a protein expressed by kidneys and choroid plexus, with anti-aging properties. Fibroblast growth factor 23 (FGF-23) is a hormone secreted by osteocytes with actions on mineral metabolism. The purpose of study was to explore the status of concentration of klotho and FGF23 in the cerebrospinal fluids (CSF) of patients with narcolepsy. Methods: 59 patients with narcolepsy and 17 individuals were enrolled. We used a radioimmunoassay technique, human klotho enzyme-linked immunosorbent assay (ELISA), human intact FGF23 ELISA and spectrophotometry to measure hypocretin-1, klotho, FGF-23 and phosphorus, respectively. T-Student Test was used to compare klotho and phosphate concentrations and Mann-Whitney U Test was used to compare FGF-23 levels between groups. ANOVA Test was used to compare klotho and phosphate CSF concentrations among narcolepsy patients with CSF hypocretin-1 <110pg/ml (HCRT-) and narcolepsy patients with CSF hypocretin-1 >110pg/ml (HCRT+) versus control subjects. Results: Klotho and phosphorus CSF levels were lower in narcoleptic patients than in control (908.18 ± 405.51 versus 1265.78 ± 523.26 pg/ml; p=0.004 and 1.34 ± 0.25 versus 1.58 ± 0.23 mg/dl; p= 0.001, respectively). We found higher median FGF-23 levels in narcoleptic patients (5.51 versus 4.00 RU/ml; p= 0.001). Klotho and phosphorus CSF levels were lower in both HCRT-/HCRT+ than controls (892.63 ± 388.34/ 925.95 ± 430.76 versus 1265.78 ± 523.26 pg/ml; p=0.014 and 1.35 ± 0.28/ 1.33 ± 0.22 versus 1.58 ± 0.23 mg/dl; p= 0.004). Moreover, we found higher median FGF-23 levels in both HCRT-/HCRT+ groups versus controls (5.51/ 6.02 versus 4.00 RU/ml in controls), p= 0.009. Conclusion: Patients with narcolepsy have decreased CSF concentration of klotho and increased CSF levels of FGF-23. These findings may play a role in understanding the pathogenesis of narcolepsy. Support: